Proposed new design for Fidani Chocolate Retail at Lot 201 A/C, Level 3, Ampang Mall, Suria KLCC, 50088 Kuala Lumpur / Muhammad Izhan Abd. Aziz - Abd. Aziz, Muhammad Izhan (Faculty of Architecture, Planning and Surveying, 2008)
The purpose of this project is to create a new design retail where present the image of Fidani chocolate itself and provide a place that suitable for Fidani’s target market. The objectives are to make sure that the concept and image blends well with Fidani’s exclusive chocolate image. To promote Fidani’s chocolate to everyone especially to chocolate indulgers. To create the comfortable place for customer to enjoy the finest chocolate made. These objectives are to aim one mission which is to apply and represent Fidani image in this retail. There are a few ways of research application in this project which are site analysis, interview and case study. The purpose these methods are made to solve the problems in the design process. The process of data collection will be applied in design process to create better space that is more comfortable and suits for everyone. In conclusion, the retail is based on research and data collection. Furthermore, the result of research is the outcome of concept and image that applied in design process.